Subcontract between the Democracy International, Inc. and Institute of Governance Studies, BRAC University (2011) - Democracy International; Institute of Governance Studies, BRAC University (Democracy International and Institute of Governance Studies, BRAC University, 2013)
The purpose of this Subcontract (the "Subcontract" or the "Contract"), dated effective as of [blank] is to set out the Contract between Democracy International, Inc., located at 4802 Montgomery Lane, Bethesda, MD 20814 ("DI" or "Prime Grantee"), and [blank], located at [blank] ("[blank]" or "Subcontractor") relating to services to be provided by Subcontractor to DI under a cooperative agreement between DI and the U.S. Agency for International Development (USAID) for Democratic Participation and Reform in Bangladesh (the "Project"), This Subcontract specifies the terms, conditions, and limits of authorization with respect to the services to be provided by Subcontractor.